A simple singing [large type] - Gould, Leslie, 1962- (Gould, Leslie, 1962- Sisters of Lancaster County, 2018)
"Marie Bachmann has always been the good Amish daughter. But when two men, a Mennonite farmhand and a bishop's rebellious son, show interest in her, she finds herself at a crossroads. Traveling to Florida and back, she grapples with her heart, finding inspiration and hope for the future in the story of a brave Civil War era ancestor"--